Feminism Analysis in the Novel “Woman at Point Zero” - Eka Wilany (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
Feminism, as a movement of a woman to demand equality and justice, fight for sexist exploitation and oppression. The movement is triggered by the awareness that the women have equal right with me. In society, woman discriminated by rules and culture. By all means, women can not accept the action of society that makes them intimidated. The methodology of the study was descriptive qualitative. Woman at Point Zero by Nawal El-Sadawi is a novel describes how hard the condition of a woman, named Firdaus, who wanted to struggle her rights, not only as a woman but also as human. The study described about feminism, a woman struggle for their rights that found in the Novel. Firdaus had to crouch, because she killed a pimp who wanted to price her, before she was on gallows. She did not feel fear of die, whereas she felt that she became a free woman without man around. She struggle for her right as woman by defending to be passive for all that accussed to her. Keywords: feminism, analysis, novel